LONG-TERM ANTHROPOMETRIC AND METABOLIC EVALUATION OF HEALTHY NEWBORNS WITH INTRAUTERINE GROWTH RESTRICTION - Mariana-Lacramioara; Andreea-Luciana Avasiloaiei; Mihaela Moscalu; Cristina Dimitriu; Maria Stamatin (Amaltea Medical Publishing House, 2018)
Introduction. Birth weight is the most significant anthropometric indicator of the clinical status of neonates. Intrauterine growth restriction (IUGR) is the cause of increasing death rate in neonates and is associated with adult cardiovascular disease and metabolic syndrome. The purpose of our study is to evaluate the relationship between IUGR, the development of children and metabolic complications in children up to the age of five. Material and methods. We performed a prospective study over a period of 4 years (2010-2013) on a group of 622 newborns with IUGR without any reported conditions during the neonatal period. The nutritional status assessment was performed by determining the weight, length, body mass index and their integration according to age and sex, on the growth curves proposed by the World Health Organization and was compared to that of 627 IUGR infants admitted to the Neonatal Intensive Care Unit. The triglyceride, cholesterol and glucose levels were evaluated and compared with normal values for age. Results. The obesity incidence (16.1%) is significant higher (χ2=32.23, p<<0.01, 95%CI). 57.6% of cases with BMI above the normal range, and overweight increases with age (29% in 2-year-olds, vs. 56.7% in 5-year-olds). The obesity incidence decreases with age (32.9% in 2-year-old, vs. 9.1% in 5-year-olds). The evaluation of the metabolic syndrome: 18% of the investigated children had hyperglycemia, and cholesterol and triglycerides levels (f =10.34, p=0.00001, 95%CI) increase with age. 32.8% of the evaluated children had cholesterol levels above 170 mg/dl. Conclusions. Overweight and obesity incidence among children born with IUGR are increased compared to the general population. It is necessary to establish the relationship between the eating habits and the studied parameters, that could elucidate the relationship of the increasing weight and the biochemical parameters (triglycerides and cholesterol).